KAJIAN KRITIK METODOLOGIS: KONSEP CINTA DAN POLA HUBUNGAN GURU-MURID PERSPEKTIF KAHLIL GIBRAN DALAM TINJAUAN PAI - Ayub Kumalla; Sovia Mas Ayu; Darul Mustofa; Ahmad Saeful Ahyar; Akbar Rahman (STKIP Pesisir Selatan, 2026)
This study aims to critically examine the concept of love and teacher–student relationship patterns from the perspective of Kahlil Gibran and analyze their relevance within Islamic Religious Education (PAI). This study is motivated by the growing need to develop pedagogical relationships that extend beyond knowledge transmission to encompass character formation, human values, and students’ spiritual development. Methods: This research employed a qualitative approach using a library research method. Data were collected from Kahlil Gibran’s major works and supported by contemporary literature on Islamic education. The analysis was conducted through a methodological critique approach, focusing on epistemological and pedagogical dimensions. Results: The findings reveal that Gibran’s concept of love emphasizes freedom, autonomy, respect for individual potential, and spiritual growth. This concept gives rise to a dialogical, humanistic, and non-authoritarian teacher–student relationship, fostering a more participatory learning environment. However, from the perspective of Islamic Religious Education, this concept requires reconstruction because it tends to reflect a humanistic-individualistic orientation without a sufficiently strong theological foundation. Furthermore, the proposed teacher–student relationship pattern may weaken the educator’s role as a moral and spiritual guide if implemented without a clear Islamic value framework. Novelty: This study offers a methodological critique that integrates literary-philosophical thought with the epistemology of Islamic education and proposes a love-based pedagogical model grounded in tauhid (Islamic monotheism). This model combines humanistic, dialogical, and spiritual values as the foundation for developing teacher–student relationships in Islamic Religious Education.